Arsenic, Zinc, and Aluminium Removal from Gold Mine Wastewater Effluents and Accumulation by Submerged Aquatic Plants (Cabomba piauhyensis, Egeria densa, and Hydrilla verticillata). (12th September 2013) - Abu Bakar, Ahmad Farid; Yusoff, Ismail; Fatt, Ng Tham; Othman, Faridah; Ashraf, Muhammad Aqeel
Abstract : The potential of three submerged aquatic plant species ( Cabomba piauhyensis, Egeria densa, and Hydrilla verticillata ) to be used for As, Al, and Zn phytoremediation was tested. The plants were exposed for 14 days under hydroponic conditions to mine waste water effluents in order to assess the suitability of the aquatic plants to remediate elevated multi-metals concentrations in mine waste water. The results show that the E. densa and H. verticillata are able to accumulate high amount of arsenic (95.2%) and zinc (93.7%) and resulted in a decrease of arsenic and zinc in the ambient water. On the other hand, C. piauhyensis shows remarkable aluminium accumulation in plant biomass (83.8%) compared to the other tested plants. The ability of these plants to accumulate the studied metals and survive throughout the experiment demonstrates the potential of these plants to remediate metal enriched water especially for mine drainage effluent. Among the three tested aquatic plants, H. verticillata was found to be the most applicable (84.5%) and suitable plant species to phytoremediate elevated metals and metalloid in mine related waste water.